Intracranial Abnormalities Are Associated With Fewer Self-Reported Symptoms in Military Service Members Following Moderate-to-Severe Traumatic Brain Injury. Issue 3 (May 2021) - Trotta, Jenna K.; Ekanayake, Vindhya; Ettenhofer, Mark L.; Hungerford, Lars D.; Lange, Rael T.; Bailie, Jason M.; Brickell, Tracey A.; Kennedy, Jan E.; French, Louis M.
Abstract : Objective: This study examined the relationship between intracranial abnormalities (ICAs) and self-reported neurobehavioral and posttraumatic stress (PTS) symptoms in members of the military with moderate-to-severe traumatic brain injury (msTBI). Method: Participants included 539 members of the US military with nonpenetrating msTBI. Self-reported neurobehavioral and PTS symptoms were assessed using the Neurobehavioral Symptom Inventory and the PTSD Checklist–Civilian Version. ICAs were categorized as present/absent (by subtype) based upon medical record review. Spearman rank-order correlations and stepwise multiple regression analyses examined univariate and combined predictive relationships between ICAs and self-reported symptoms. Results: The presence of any ICA was associated with reduced self-reported neurobehavioral and PTS symptoms. ICA-associated reductions were largest for PTS, followed by affective and cognitive neurobehavioral symptoms, and relatively weak for somatic/sensory and vestibular symptoms. Effects of different types of ICAs were comparable. Greater time since injury was related to greater symptom report, whereas duration of loss of consciousness and posttraumatic amnesia were not consistently related to self-reported symptoms. Conclusions: Results suggest that ICAs are associated with suppression of reported PTS and neurobehavioral symptoms—potentially via reduction in self-awareness. These findings support comprehensive, objective evaluation to identify impairments in self-awareness and functioning in msTBI patients.